PENGARUH KOMPETENSI SOSIAL DAN KECERDASAN SPRITUAL TERHADAP MORAL KERJA GURU SMP NEGERI DIKECAMATAN MINAS KABUPATEN SIAK - Kurnia Widiastuti; Isjoni Isjoni; Nurpit Junus (Universitas Riau, 2017)
This study aims to analyze: (1) the influence of social competence on workmorale, (2) the influence of spiritual intelligence on work morale (3) the influence of socialcompetence and spiritual intelligence on teacher work morale. The research method used isquantitative research method by using survey method. The population in this study is all teachersof SMP Negeri in Kecamatan Minas Siak Regency amounted to 128 teachers and the numberof samples in this study as many as 97 teachers. The research instrument used for data collectionis a questionnaire. Before the instrument (questionnaire) research used to collect researchdata, firstly conducted trials conducted with validity and reliability test Test requirements analysisis a test of normality and linearity, then conducted data analysis with correlation test, simpleand multiple regression. The result of this research is found: (1) there are positive and significantinfluence of social competence to teacher work moral equal to 34,8%; (2) there is positive andsignificant influence of spiritual intelligence and to teacher work moral equal to 36,8%; (3)There are positive and significant influence of social competence and spiritual intelligence toteacher work morale equal to 42,6%. The higher the influence of social competence andspiritual intelligence then the higher also in affecting the moral work of teachers in SMP Negeriin Kecamatan Minas Siak District. Thus, to optimize work morale teachers need improvementin social competence and spiritual intelligence.